UPAYA MEMPERPANJANG MASA SIMPAN ANDALIMAN (Zanthoxylum acanthopodium D) STUDI KASUS DESA BANDAR HUTA USANG KABUPATEN DAIRI - Roida E. Sinaga; Healthy A. Prasetyo (JURNAL AGROTEKNOSAINS, 2019)
Andaliman (Zanthoxylum acanthopodium DC.) is a plant with characteristic is easily rotten and moldy, so postnatal care is needed after harvest. The proper method is preservation technique. This study was meant to know the effect of the CaCl2 (Calsium chloride) applications on long-storage andaliman (Zanthoxylum acanthopodium DC).In previous study came the result that its best treatment was with infantile andaliman with Calsium chloride at a concentration of 0,45% for 40 minutes. On this research will be applied Calsium chloride 0,45% to see the old influence of andaliman storage. Andaliman will be stored at an old level of storage 4 days, 5 days, 6 days and 7 days. The parameters observed are water levels, weight shards, oil levels and organological tests of color, scent and texture. Research usess the complete design methods of factorial design that long storage consist of 4 levels L1=4 days : L2=5 days : L3=6 days : L4=7 days. This study has the target of the publication of a scientific article in the national journal with ISSN. It refers to postexilic technologies and engineering food processing technologies of diversified and illiegal agricultural products. The benefit of this study yielded an underlying theory that could be used as afurther research reference and useful to a society of farmers who would market andaliman.